2022
DOI: 10.1177/10711007211064609
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Findings and First Metatarsal Rotation in Hallux Valgus

Abstract: Background: Failure to identify and correct malrotation of the first metatarsal may lead to recurrent hallux valgus deformity. We aimed to identify the proportion of hallux valgus patients with increased first metatarsal pronation using weightbearing computed tomography (WBCT) and to identify the relationship with conventional radiographic measurements. Methods: WBCT scans were analyzed for 102 feet with a hallux valgus angle (HVA) and intermetatarsal angle (IMA) greater than or equal to 16 and 9 degrees, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 92 publications
0
16
0
Order By: Relevance
“…Recent studies have confirmed that there is considerable rotation of the first metatarsal in hallux valgus deformity, which should be corrected as part of the overall deformity correction. 8,41,49,57,58 A transverse osteotomy potentially allows better rotational control and correction of the head compared to a chevron. As a transverse osteotomy is inherently unstable, it does have to be controlled with a reduction maneuver during fixation; otherwise, there is a risk of malunion in the sagittal plane.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have confirmed that there is considerable rotation of the first metatarsal in hallux valgus deformity, which should be corrected as part of the overall deformity correction. 8,41,49,57,58 A transverse osteotomy potentially allows better rotational control and correction of the head compared to a chevron. As a transverse osteotomy is inherently unstable, it does have to be controlled with a reduction maneuver during fixation; otherwise, there is a risk of malunion in the sagittal plane.…”
Section: Discussionmentioning
confidence: 99%
“…The percutaneous technique also allows rotational correction of the first metatarsal, which is increasingly recognized as an important factor leading to recurrence. 10,36,44 We did not find any evidence of radiographic osteoarthritis of the first TMTJ joint in the long-term follow-up radiographs. It should be noted that with increasing shifts (>~75%), the chevron cut does not impede rotational correction.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, even when IMA correction results in sesamoid reduction, it may not be adequately reflected by sesamoid grade on weightbearing AP radiographs, and conversely apparent reduction on AP standing radiographs may not indicate reduction of the metatarso-sesamoid complex. 16 Twodimensional weightbearing AP radiographs after surgery may be limited in evaluating 3-dimensional deformities. [12][13][14] The accuracy of HVA, IMA, and TSP measurements in this study was enhanced by setting the reference line as the line from the center of the distal head to the proximal end of the diaphysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even when IMA correction results in sesamoid reduction, it may not be adequately reflected by sesamoid grade on weightbearing AP radiographs, and conversely apparent reduction on AP standing radiographs may not indicate reduction of the metatarso-sesamoid complex. 16 Two-dimensional weightbearing AP radiographs after surgery may be limited in evaluating 3-dimensional deformities. 12-14…”
Section: Discussionmentioning
confidence: 99%